Price dynamics for agriculture and nutrition policy: An advanced learning event organized by the International Food Policy Research Institute - Benimana, Gilberthe Uwera; Warner, James (International Food Policy Research Institute, 2024)
IFPRI presentation give in Kigali, Nyamata 29-31 May 2024. With contributions from Mugabo Serge.